2015
DOI: 10.1039/c5an00112a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of cocaine, benzoylecgonine and methylecgonine in fingerprints using surface mass spectrometry

Abstract: Latent fingerprints provide a potential route to the secure, high throughput and non-invasive detection of drugs of abuse. In this study we show for the first time that the excreted metabolites of drugs of abuse can be detected in fingerprints using ambient mass spectrometry. Fingerprints and oral fluid were taken from patients attending a drug and alcohol treatment service. Gas chromatography mass spectrometry (GC-MS) was used to test the oral fluid of patients for the presence of cocaine and benzoylecgonine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 19 publications
0
74
0
Order By: Relevance
“…The image of this fragment ion is presented as an inset, showing some ridge detail. Whilst MALDI has been used before in imaging mode on fingerprints spiked with cocaine [20] and in profiling mode to detect cocaine in the fingerprint of a drug user [19], this appears to be the first report of MALDI imaging of drugs in a fingerprint from a drug user. Whilst quantification of substances in fingerprint residue using MALDI is known to be difficult to achieve [22], a two-step process of (a) quantification of a drug residue in a fingerprint using LESA, and then (b) imaging using MALDI would thereby provide quantification and visualisation of a drug metabolite within a fingerprint ridge.…”
Section: Analysis Of Patient Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The image of this fragment ion is presented as an inset, showing some ridge detail. Whilst MALDI has been used before in imaging mode on fingerprints spiked with cocaine [20] and in profiling mode to detect cocaine in the fingerprint of a drug user [19], this appears to be the first report of MALDI imaging of drugs in a fingerprint from a drug user. Whilst quantification of substances in fingerprint residue using MALDI is known to be difficult to achieve [22], a two-step process of (a) quantification of a drug residue in a fingerprint using LESA, and then (b) imaging using MALDI would thereby provide quantification and visualisation of a drug metabolite within a fingerprint ridge.…”
Section: Analysis Of Patient Samplesmentioning
confidence: 99%
“…The field of fingerprint chemical analysis is also a rapidly growing research area, starting from a recent paradigm shift in the forensic community for using fingerprints for more than just their ridge detail [21][22][23][24][25][26][27][28][29]. It has been previously shown that the chemical composition relates to the age of a latent fingerprint [28], the sex of the donor [24], their drug habits or medical history [17][18][19][20], the way they interact with development reagents [21] and might even be used to confirm their identity using their amino acid profile [29] or to verify their location on questioned documents [23]. This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database.…”
Section: Introductionmentioning
confidence: 99%
“…One potential application that has proven to be successful for the detection of trace amounts of exogenous compounds is MALDI ion mobility separation tandem mass spectrometry (MALDI-IMS-MS/MS) which can add confidence to the identification of any detectable species and has been successfully employed previously for the detection of excreted drug metabolites in latent fingermark samples 24 .…”
Section: Throughout the Experiments Performed Usingmentioning
confidence: 99%
“…While methods exist for the direct chemical analysis of fingerprint residues, they rely on the introduction of the entire fingerprint into either a solvent or an analytical instrument in order to detect the presence of certain analytes on a fingerprint. 15 This is not ideal for forensic investigators as it requires destruction of the fingerprint ridge detail, or specialised equipment to perform surface analysis at a crime scene. Hydrogels would provide a flexible solution to sample collection as they can be applied to non-porous surfaces.…”
Section: 11mentioning
confidence: 99%